1996
DOI: 10.1148/radiology.198.3.8628874
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional H-1 MR spectroscopic imaging of the in situ human prostate with high (0.24-0.7-cm3) spatial resolution.

Abstract: These results suggest that a 3D MRSI examination added to a clinical MR imaging examination may help define the presence and spatial extent of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
397
1
10

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(423 citation statements)
references
References 0 publications
15
397
1
10
Order By: Relevance
“…This is in agreement with previous studies that have shown the highest citrate/choline ratios in the peripheral zone (2,24).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is in agreement with previous studies that have shown the highest citrate/choline ratios in the peripheral zone (2,24).…”
Section: Discussionsupporting
confidence: 94%
“…MAGNETIC RESONANCE SPECTROSCOPIC IMAGING (MRSI) of the prostate yields high sensitivity and specificity in the localization of prostate cancers (1)(2)(3)(4). Cancer detection is achieved by mapping the relative concentrations of metabolic markers of disease-citrate, choline, and creatine-throughout the prostate.…”
mentioning
confidence: 99%
“…Many magnetic resonance spectroscopy (MRS) studies of choline metabolism have shown increased levels of total Cho (tCho) in cancers developing in different organs, such as brain, 1-5 prostate [6][7][8] and breast. [9][10][11][12][13] The increase of tCho in tumors has become a potentially important biomarker in cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, owing to the overlap of spectral peaks, the composite metabolite ratio (choline + spermine + creatine)/citrate is usually measured from prostate spectra, using integration. There are only a few instances where absolute concentrations of citrate, creatine, and choline have been measured, using either integration or metabolite fitting 8, 9, 10, 11, 12…”
mentioning
confidence: 99%